Use of Distribution of F-Latency (DFL) in the Detection of Cervical Spondylotic Neuropathy - Hossain, Md Iftekhar; Chowdhury, Ehsan Alam; Mamun, AA; Salam, A; Baig, Tanvir Noor; Rabbani, K Siddique-e (Bangladesh Journal of Medical Physics, 2013)
Distribution of F-latencies (DFL) is a new nerve conduction parameter introduced by our laboratory to give a distribution of the conduction velocity (DCV) of motor nerve fibres in a peripheral nerve trunk simply as its mirror image. Earlier work revealed an association between Cervical Spondylotic (CS) neuropathy and DFL patterns obtained from the thenar muscle at the base of the thumb by artificially stimulating the median nerve. DFL froom normal subjects had a single peaked pattern, while that from subjects with CS had double or triple peaks, or a broad peak. The broad peak was suggested to be an indicator of early CS, even when the symptoms are not fully apparent. This led to some hypotheses based on physics, physiology and statistics, in order to explain such patterns. In order to verify these hypotheses, experiments need to be carried out carefully, and the present work is a step towards that goal. In this work DFL of the median nerve was obtained from 15 subjects, 6 normal, and 9 with diagnosed cervical spondylosis. The latter were subjected to further X-ray and MRI investigations, performed blindly at regular clinics. All of the 9 subjects were identified with either compression of nerve roots (radiculopathy), or spinal cord compression due to the bulging of the inter-vertebral discs (myelopathy). This shows with confidence that double or triple peaks of DFL indeed relates to CS, and broad peaks indicate their early stage. The same concept may be extended to other peripheral nerves, both in the hands and legs. Thus DFL may become an important screening test for neuropathy, as a first choice, offering a low cost and widely available test compared to the only other alternative, MRI, for such diagnosis. DOI: http://dx.doi.org/10.3329/bjmp.v4i1.14676 Bangladesh Journal of Medical Physics Vol.4 No.1 2011 37-42